Measurement of aerodynamic forces and flow field of a soccer ball in a wind tunnel for knuckle effect - Murakami, M.; Kondoh, M.; Iwai, Y.; Seo, K. (Procedia Engineering, 2010)
Wind tunnel experiments have been conducted to investigate the knuckle effect of a soccer ball. In the present experiment, we measured the surface pressure of a ball as well as aerodynamic forces, and made tuft grid visualization to investigate wake structure behind a ball. We are in particular interested in the seemingly random nature of the knuckle effect resulting from the movement of vortical structure behind a ball in the super critical Re range and in the detailed mechanism causing the knuckle effect. Discussion will also refers to knuckle balls of baseball and volleyball.